The count of monte cristo ebook - Dumas, Alexandre (Duke Classics, 2012)
The Count of Monte Cristo is Alexandre Dumas' classic tale of revenge and adventure. The young sailor Dantes is fallaciously charged with treason and loses his fiancé, his dreams and his life when he is locked up for thirteen years on the island prison of Chateau d'If. Mentored by another prisoner, Dantes finally escapes the prison, reinvents himself as the Count of Monte Cristo and begins to exact his revenge on the people who set him up.